The PELATIHAN DAN IMPLEMENTASI CD INTERACTIVE UNTUK MENINGKATKAN KEMAMPUAN LISTENING SISWA PADA MATA PELAJARAN BAHASA INGGRIS DI SMA DEK PADANG: Herfyna Asty, dan Riny Dwitya Sani - Herfyna Asty; Riny Dwitya Sani (Pengabdian Masyarakat Ilmu Pendidikan, 2022)
Language skills, starting from learning to listen to the language, then speaking, then learning to read and write. The four skills are basically a unified competency that must be mastered by students in language learning. To achieve these competencies requires a long learning process and is carried out in earnest.One way that can be done to improve listening skills, in particular, is to use appropriate and interesting media for students. One of the media that can be used is CD Interactive. Therefore, the service team for the English Education Study Program STKIP PGRI West Sumatra wants to implement Interactive CDs to improve students' listening skills at SMA DEK Padang